Between Tradition and Profession: Intersectionality of Javanese Women Journalists in Surakarta’s Newsroom - Hakim, Rahman; Riski, Vanggi Eka (JURNAL KOMUNIKASI INDONESIA, 2026)
Javanese female journalists in Surakarta navigate the simultaneous pressures of professional journalism and deeply internalised Javanese cultural values such as nrimo (acceptance of one’s circumstances), andhap asor (humble and deferential conduct), and tepa selira (attentiveness to the feeling of others). These values shape their everyday conduct in the newsroom yet often remain unacknowledged in existing literature. Combining Intersectionality Theory, Face-Negotiation Theory (Ting-Toomey), and Self Theory (Rogers) as complementary frameworks, this qualitative study adopts a constructivist paradigm and employ phenomenological method to explore how female journalists make sense of the intersection between gender norms and local cultural values. Data were collected through in-depth semi-structured interviews and newsroom observation. The findings reveal four themes: the internalisation of Javanese values shapes professional conduct; dual identities as women and journalists are experienced differently depending on marital status and domestic responsibilities; identity negotiation strategies emerge from structural position rather than individual character; and responses to verbal sexual harassment reflect the interplay of cultural values, hierarchical position, and situational context. This study demonstrates that, even within a single cultural setting, differing structural positions generate diverse experiences that cannot be generalised across individuals. Keywords: Javanese female journalists, intersectionality, Javanese culture, newsroom, phenomenology